.NET Windows Forms custom controls - Weeks, Richard, 1972- (Sams, 2002)
The intent of this book is to teach .NET developers the skills necessary to create their own leading edge custom controls. The art of creating custom controls has never been truly explored in detail, often the examples provided are trivial and do not begin to explore the requirements need for a commercial quality custom control. This book will not only provide that knowledge, but, in addition provide the source for a fully functional Outlook Bar control.